The short-term outcome of intracranial stenosis with distal thrombosis treated with balloon-assisted tracking - Li, Hui; Meng, Xiangyu; Mao, Kai; Liu, Linlin; Xu, Lifeng; Chen, Lingyou; Xu, Can; Wang, Wenqing; Li, Conghui (Frontiers in Neurology, 2024)
Background and purposes: Treating intracranial stenosis with distal thrombosis (IS&DT) using traditional mechanical thrombectomy (MT) techniques has proven challenging. This study aims to summarize the experience of utilizing the Balloon-assisted tracking (BAT) technique for IS&DT. Methods: Demographic and morphologic characteristics of patients with IS&DT were collected for this study. Various parameters were recorded, including the sequence of vascular re-perfusion, the puncture-to-reperfusion time (PRT), the residual stenosis rate, and the occurrence of re-occlusion. The Thrombolysis in Cerebral Infarction (TICI) scale was used to assess the reperfusion of intracranial vessels, with a TICI score of ≥2b considered as successful perfusion. The clinical status of patients was evaluated at three time points: pre-procedure, post-procedure, and at discharge using the modified Rankin score (mRS). Results: In this study, a total of 10 patients were diagnosed with IS&DT, consisting of 9 male patients (90.0%) and 1 female patient (10.0%). The patients' mean age was 63.10 years (ranging from 29 to 79 years). The mean National Institute of Health Stroke Scale (NIHSS) score before treatment was 24.3 (ranging from 12 to 40), indicating the severity of their condition. Following the procedure, all patients achieved successful reperfusion with a Thrombolysis in Cerebral Infarction (TICI) score of ≥2b. The average puncture-to-reperfusion time (PRT) was 51.8 minutes (ranging from 25 to 100 minutes), indicating the time taken for the procedure. During the perioperative period, 3 patients (30.0%) experienced complications. One patient had hemorrhage, while two patients had contrast extravasation. Among these cases, only the patient with hemorrhage (10%) suffered from a permanent neurological function deficit. At discharge, the patients' condition showed improvement. The mean NIHSS score decreased to 13.2 (ranging from 1 to 34), indicating a positive response to treatment. The mean mRS score at discharge was 3.2 (ranging from 1 to 5), showing some level of functional improvement. Conclusion: In conclusion, the use of the Balloon-assisted tracking (BAT) technique for treating intracranial stenosis with distal thrombosis (IS&DT) showed promising results. However, a moderate rate of perioperative complications was observed, warranting further investigation and refinement of the procedure.